ANIMAL-BASED OR PLANT-BASED DAIRY FOODS IN THE INDIAN CONTEXT - A REVIEW - Singh, Keshav (Global journal of Business and Integral Security, 2022)
This review paper analyses the impact of the growth of dairy food, both plant- and animal-based, through a food systems approach in the Indian context. The review’s primary purpose was to find solutions that will provide a sufficient supply of healthy food to India’s growing population while remaining within environmental constraints. In addition, it looked for answers to fundamentals of nutrition, the livelihood of small farmers and the implications of the growth of dairy foods in the Indian set-up. Articles included in this review are identified through conventional keyword searching strategies, published papers’ bibliographies, and sustainability-related journal searches. Studies on plant-based dairy foods were found to be either non-existent or sparse, with India as their focal focus and their impact on traditional dairying. No study found a link between livelihood, nutrition, and sustainability within the Indian context having a central theme of plant dairy foods and their relationship with existing dairy industry dynamics.